Penerapan Model Pembelajaran Problem Based Learning dengan Pendekatan Culturally Responsive Teaching (CRT) untuk Meningkatkan Hasil Belajar Matematika. - Ismawati; Baidowi; Sari, Baiq Lita Juwita (Mataram University, 2025)
The purpose of this study was to improve mathematics learning outcomes on the topic of Two-Variable Linear Equation Systems through the implementation of the Problem-Based Learning (PBL) model integrated with the Culturally Responsive Teaching (CRT) approach in Class VIII G of SMPN 8 Mataram. This research employed a Classroom Action Research (CAR) method adapted from the Kemmis and McTaggart model and was conducted in two cycles. Each cycle consisted of four main stages: planning, action implementation, observation, and reflection. The results showed a significant improvement in student learning outcomes from the pre-cycle to Cycle II. The average student score increased from 78.055 in the pre-cycle to 84.583 in Cycle II, while the percentage of students achieving the Minimum Mastery Criteria (KKM) rose from 58.333% to 94.444%. These findings indicate that the application of the Problem-Based Learning (PBL) model combined with the Culturally Responsive Teaching (CRT) approach was not only effective in enhancing students’ understanding of the material but also in increasing their engagement during the learning process. In addition, integrating PBL with Culturally Responsive Teaching (CRT) fostered an inclusive learning environment, respected students’ cultural diversity, and supported the development of stronger critical thinking and problem-solving skills.